2009
DOI: 10.1099/mic.0.029439-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface expression of adhesins for fibronectin correlates with virulence in Sporothrix schenckii

Abstract: The virulence of four Sporothrix schenckii isolates was compared in a murine model of sporotrichosis, together with the protein pattern of the yeast cell surface and the capacity to bind the extracellular matrix protein fibronectin. Virulence was determined by the mortality rate, fungal burden and histopathology. Two clinical isolates were more virulent for C57BL/6 mice, but no direct correlation was seen between virulence and the clinical or environmental origin of the isolates. The lowest virulence was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 30 publications
0
43
0
2
Order By: Relevance
“…Some studies have demonstrated that the fungus has integrins or adhesin lectinlike molecules that recognize human fibronectin at several points on the molecule (135). The fibronectin adhesins are located on the surface of yeast cells, and their expression is related to fungal virulence (251). It is also known that these fibronectin receptors are different from laminin receptors (133).…”
Section: Adhesionmentioning
confidence: 99%
“…Some studies have demonstrated that the fungus has integrins or adhesin lectinlike molecules that recognize human fibronectin at several points on the molecule (135). The fibronectin adhesins are located on the surface of yeast cells, and their expression is related to fungal virulence (251). It is also known that these fibronectin receptors are different from laminin receptors (133).…”
Section: Adhesionmentioning
confidence: 99%
“…Specific microbial adhesins mediate adherence to host tissues by participating in sophisticated interactions with some of the host proteins that compose the extracellular matrix (Teixeira et al, 2009). The adhesinencoding genes are not constitutively expressed.…”
Section: The Expression Of Adhesinsmentioning
confidence: 99%
“…Otra forma de medir la mortalidad que puede llegar a producir es su capacidad de unirse a la fibronectina vía las adhesinas de su superficie, un factor de virulencia que permite la invasión y diseminación a tejidos más profundos (20).…”
Section: Introductionunclassified